GAL4-based functional screen of neuropeptides in Drosophila reproduction - Madhumala K. Sadanandappa; Caliope Marin; Shinae Park; Shivaprasad H. Sathyanarayana; Giovanni Bosco (PLoS ONE, 2026)
Neuropeptides are evolutionarily conserved signaling molecules that regulate diverse behavioral and physiological processes, including reproduction. Although, several neuropeptides have established roles in reproductive regulation, the reproductive functions of many neuropeptides in Drosophila melanogaster remain poorly characterized. Here, we performed a targeted neurogenetic screening to systematically assess the contribution of 25 neuropeptides to reproductive output. Using neuropeptide-specific GAL4 drivers and synaptic silencing with tetanus toxin, we quantified the egg-laying as an integrated functional readout of reproduction. Disruption of 14 neuropeptides altered egg-laying, including eight neuropeptides not previously described to play roles in reproductive regulation. While some of these effects are likely indirect and may reflect contributions from both female and male flies or systematic physiological signaling, these results reveal broad involvement of neuropeptidergic pathways in reproductive function. Collectively, this study establishes a functional screening framework, identifies new reproductive neuropeptides, and provides a curated resource to guide future mechanistic studies of neuropeptide-mediated brain-gonad communication.